Perbandingan Tepung Biji Dengan Pure Terhadap Velva Durian Durio zibethinus - Asmiran M. Saleh; Suriana Laga; Fatmawati Fatmawati (PALLANGGA: Journal of Agriculture Science and Research, 2023)
Durian is a type exotic tropical fruit plant that has a unique taste and aroma and a lot of production. Durian seed waste can be used as durian seed flour. Durian seed flour can be used as a food ingredient such as velva (frozen dessert). This study aims to determine the ratio of durian seed flour to fat content, overrun and and melting power as well as organoleptic tests which include taste, aroma, color and texture produced. The research treatment was the comparison of durian seed flour and pure durian (70% : 30%), (75% : 25%), (80% : 20%), and (85% : 15%). Data analysis using Complete Randomized Design (RAL) with four treatment levels and three replications. Observational data were analyzed using analyzed using analysis of variance (ANOVA) and the smallest real difference follow-up test. Comparison of durian seed powder and durian puree had a very significant effect on fat content, overrun, taste, aroma, color, and texture but had no significant effect on melting time. The best treatment results from velva durian were the comparison of 85% durian seed flour and 15% puree durian in terms of fat content 0,13%, overrun 33,82%, melting time 44,45 minutes, taste 2,81% (didn’t like it), aroma 3,06 (rather like), color 3,44 (rather like), and texture 3,36 (rather like). Durian merupakan salah satu jenis tanaman buah tropis eksotik yang mempunyai rasa dan aroma yang unik serta produksinya yang banyak. Limbah biji durian dapat dijadikan tepung biji durian. Tepung biji durian dapat dimanfaatkan sebagai bahan makanan seperti velva (makanan beku). Penelitian ini bertujuan untuk mengetahui perbandingan tepung biji durian terhadap kadar lemak, overrun, dan daya leleh serta uji organoleptik yang meliputi rasa, aroma, warna dan tekstur yang dihasilkan. Perlakuan penelitian yaitu perbandingan tepung biji durian dan pure durian (70% : 30%), (75% : 25%), (80% : 20%), dan (85% : 20). Analisis data menggunakan metode Rancangan Acak Lengkap (RAL) dengan empat taraf perlakuan dan tiga kali ulangan. Data hasil pengamatan dianalisis menggunakan analisis keragaman (ANOVA) dan uji lanjutan Beda Nyata Terkecil. Perbandingan tepung biji durian dan pure durian berpengaruh sangat nyata terhadap kadar lemak, overrun, rasa, aroma, warna, dan tekstur tetapi tidak berpengaruh nyata terhadap daya leleh. Hasil perlakuan terbaik dari velva durian adalah perbandingan tepung biji durian 85% dan pure durian 15% ditinjau dari kadar lemak 0,13%, overrun 33,82%, waktu leleh 44,45 menit, rasa 2,81 (tidak suka), aroma 3,06 (agak suka), warna 3,44 (agak suka), dan tekstur 3,36 (agak suka).